The Role of CEO Leadership and Project Management for Innovation Success in IT Sector of Pakistan: A Moderating Effect Of Human Capital - Butt, Hassan Daud; Aijaz, Urooj; Bano, Sofia; Shamim, Dr.Asif; Hayat, Anum; Mazhar, Marium (The journal of contemporary issues in business and government, 2021)
The purpose is to examine the effect of CEO transformational leadership, and project management best practices on innovation success with the moderating effect of human capital in IT firms of Pakistan. Using purposive sampling technique, 306 responses have been collected from the IT professionals of Karachi, Pakistan while PLS-SEM has been employed for analysis. The results have shown that CEO transformational leadership and technical aspects of project management best practices have positive effect on innovation success of IT firms while people aspects of project management best practices have no effect on innovation success of IT firms. However, human capital does not moderate the effect of CEO transformational leadership and project management best practices on IT firms’ innovation success in Pakistan. Hence, the study has suggestedthat the correct choice of tools and procedures leads to innovation, PMBP can also be used strategically by organizations. It will streamline management actions for the progress of innovation, as well as build invaluable tools for the preparation, implementation, monitoring and assessment of innovative workflows, develop improved connectivity and efficient coordination with clients.